ANALISIS PENGELOLAAN MODAL KERJA PADA PT. JASA RAHARJA (PERSERO) TBK. - Aprinsi Salombe; Johny Revo Elia Tampi; Harry J Sumampouw (Universitas Sam Ratulangi, 2017)
ABSTRACT : Working capital management involves two types of links between elements of the balance sheet. First, regarding the relationship between types of property and how to finance this treasure. Second, regarding the determination of the level of total current assets to be possesse. The purpose of this study was to analyze the extent sufficient levels of working capital at PT. Prog (Persero) Tbk. In financing operations and then contribute to the improvement of corporate profits in the future. This type of research is descriptive study researcher-evaluative. The analysis tool that I use is a comparative analysis of financial statements, analysis of sources and uses of working capital, and evaluation using working capital adequacy ratio at Pt. Prog (Persero) Tbk. These results indicate that: 1. The results of the analysis of the comparative financial statements for three periods to see the changes (up or down) of all the components, such as current assets, total assets, current liabilities, total debt and equity, an average of nearly all components increased significantly from year to year, thus contributing an increase in working capital: 2. The result of the analysis of working capital adequacy ratio was found that the level of efficiency and effectiveness of working capital management is maintained so as not found the funds idle (idle fund).Â Keywords: Working Capital Management, Comparative Financial Statements, Working Capital Adequacy Ratio.